Sustainable Development Goal (SDG) 4 Country Profile: Belize - The United Nations Educational, Scientific and Cultural Organization (UNESCO) (UNESCO, 2019)
This item contains statistics on: National Context (this section includes the main demographic and socioeconomic indicators of the country for the last available year); Education system; Free, equitable and quality primary and secondary education; Quality early childhood development, care and preprimary education; Quality TVET and tertiary education; Technical and vocational skills; Youth and adult literacy and numeracy; Education facilities; Scholarships; Qualified teachers.
Keywords: sustainable development; country profile; SDG